Subchromosomal karyotype evolution in Equidae - Musilova, P; Kubickova, S; Vahala, J; Rubes, J (Chromosome research, 2013)
Equidae is a small family which comprises horses, African and Asiatic asses, and zebras. Despite equids having diverged quite recently, their karyotypes underwent rapid evolution which resulted in extensive differences among chromosome complements in respective species. Comparative mapping using whole-chromosome painting probes delineated genome-wide chromosome homologies among extant equids, enabling us to trace chromosome rearrangements that occurred during evolution. In the present study, we performed subchromosomal comparative mapping among seven Equidae species, representing the whole family. Region-specific painting and bacterial artificial chromosome probes were used to determine the orientation of evolutionarily conserved segments with respect to centromere positions. This allowed assessment of the configuration of all fusions occurring during the evolution of Equidae, as well as revealing discrepancies in centromere location caused by centromere repositioning or inversions. Our results indicate that the prevailing type of fusion in Equidae is centric fusion. Tandem fusions of the type telomere-telomere occur almost exclusively in the karyotype of Hartmann's zebra and are characteristic of this species' evolution. We revealed inversions in segments homologous to horse chromosomes 3p/10p and 13 in zebras and confirmed inversions in segments 4/31 in African ass, 7 in horse and 8p/20 in zebras. Furthermore, our mapping results suggested that centromere repositioning events occurred in segments homologous to horse chromosomes 7, 8q, 10p and 19 in the African ass and an element homologous to horse chromosome 16 in Asiatic asses. Centromere repositioning in chromosome 1 resulted in three different chromosome types occurring in extant species. Heterozygosity of the centromere position of this chromosome was observed in the kiang. Other subtle changes in centromere position were described in several evolutionary conserved chromosomal segments, suggesting that tiny centromere repositioning or pericentric inversions are quite frequent in zebras and asses.
Keywords: molekulární evoluce; Chromosome Painting; genová přestavba; hybridizace in situ fluorescenční; karyotyp; Equidae; Chromosome Inversion; Evolution, Molecular; Karyotype; Gene Rearrangement; In Situ Hybridization, Fluorescence; chromozomální inverze; Centromere; zvířata; mapování chromozomů; malování chromozomů; centromera; Chromosomes, Artificial, Bacterial; Species Specificity; Chromosome Mapping; Telomere; telomery; druhová specificita; umělé bakteriální chromozomy; Animals